Sudan : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1999)
This paper reviews economic developments in Sudan during 1997-99. Sudan initiated reforms under the 1997 and 1998 Staff-Monitored Programs. Real GDP growth accelerated modestly to an annual average of about 6 percent during 1997-98. Inflation declined from an average of 133 percent in 1996 to 17 percent in 1998. Fiscal revenue buoyancy has increased markedly after years of stagnation at low levels and, coupled with an improvement in budget control, has succeeded in sharply reducing the overall budget deficit. Aided by positive real rates of returns, financial disintermediation has been halted.